The Factors Affecting Online Repurchase Intention in the Case of Zalora - Fortuna Shanarda Wicaksono; Hans Kristian Darsono (iBuss Management, 2018)
The market of digital economy is keep growing in Indonesia, especially for clothing industry as the most favorite product bought by Indonesian internet users. As online clothing industry is the most favorite product, the competition itself in the industry becomes tighter, which leads to the importance of knowing the online repurchase intention in clothing industry itself. This research aims to know the effectiveness of eight factors namely perceived value, perceived usefulness, perceived ease of use, functionality, firm’s reputation, security and privacy, reliability, and trust in affecting online repurchase intention in the case of Zalora.The data were gathered through simple random sampling with 130 questionnaires. Then, the data were processed using Multiple Linear Regression Analysis. It is found that all eight factors impact online repurchase intention simultaneously. However, only perceived ease of use, security and privacy, trust, firm’s reputation, and reliability impact purchase intention individually. Keyword:Perceived Ease of Use, Reliability, Security and Privacy, Trust, Online Repurchase Intention